Comparison of the nematode distribution among tidal levels between two years (2014-2015) in a NaGISA rocky shore site in Taklong Island, Southern Guimaras, Philippines. - Ruiz, Thea Krystel (2018.)
NaGisa rocky shore site in Taklong Island, Southern Guimaras was the study site involved in the assessment of nematode abundance and distribution among tidal levels for two years (2014 & 2015). Sample collection was done on September 2014 and 2015. Four transects representing different tidal levels were laid out parallel to the shore (True High Tide, True Mid Tide, True Low Tide, True Sub-Tidal) with 5 replicates every 5 meters for each transect. A total of 45 meiofaunal taxa were observed, 26 and 19 meiofaunal taxa were found in samples gatherd in 2014 and 2015 respectively. In 2014, the major groups were harpacticoid (48.71%), nematode (33.24%), polychaetes (4.64%), cumacea (1.96%), annelid (1.68%), and other (9.76%). In the 2015 samples the major groups were nematodes (68.07%), harpacticoids (21.95%), gastropod (2.47%), polychaetes (1.61%), annelid (1.68%), and others (4.23%). There were 8 nematode families found in both 2014 and 2015 samples. The most abundant nematode family in 2014 was Chromadoridae accounting for 39% of the total composition of nematodes, followed by Desmodoridae (32%), Enchelidiidae (7%), and Linhomoidae (7%), Enoplidae (5%) and Phanodermatidae (5%), Oxystominidae (3%), and Xyalide (2%). Nematode density showed a decrease as tidal level increased. This coincided with data reported by Mokievsky et al. (2007) that nematode density decreases as water depth increases parallel to productivity which decreases as tidal level increases. This trend is supported by the strong negative correlation between nematode density and macroalgal biomass and cover. As macrofaunal biomass and cover increased, nematode density decreased. Satyam et el. (2018) showed that epiphytic habitats harbored the lowest number of species.
Thesis (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo. 2018.
Keywords: Nematode -- NaGISA rocky shore -- Taklong Island, Southern Guimaras; Rocky Shore -- NaGISA; Meiofauna -- Taklong Island, Southern Guimaras; Macroalgae -- Taklong Island, Southern Guimaras